2010
DOI: 10.1561/1800000003
|View full text |Cite
|
Sign up to set email alerts
|

From Keyword Search to Exploration: Designing Future Search Interfaces for the Web

Abstract: This monograph is directed at researchers and developers who are designing the next generation of web search user interfaces, by focusing on the techniques and visualizations that allow users to interact with and have control over their findings. Search is one of the keys to the Web's success. The elegant way in which search results are returned has been well researched and is usually remarkably effective. However, analyzing innovative design approaches. We then discuss evaluations at each of these levels of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 168 publications
0
44
0
1
Order By: Relevance
“…The creation of standardised benchmarks for quantifying retrieval effectiveness (commonly known as test or reference collections) is highly beneficial when assessing system performance (Robertson, 2008;Sanderson, 2010). However, evaluation at levels 4-6 is also important as it assesses the performance of the system from the user's perspective and may also take into account the user's interactions with the system, along with broader effects, such as its impact and use in operation (Kelly, 2009;Borland, 2013;Wilson et al, 2010). In the following sections we discuss in more detail the two main approaches referenced in the literature: system-oriented and useroriented evaluation.…”
Section: Approaches To Ir Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The creation of standardised benchmarks for quantifying retrieval effectiveness (commonly known as test or reference collections) is highly beneficial when assessing system performance (Robertson, 2008;Sanderson, 2010). However, evaluation at levels 4-6 is also important as it assesses the performance of the system from the user's perspective and may also take into account the user's interactions with the system, along with broader effects, such as its impact and use in operation (Kelly, 2009;Borland, 2013;Wilson et al, 2010). In the following sections we discuss in more detail the two main approaches referenced in the literature: system-oriented and useroriented evaluation.…”
Section: Approaches To Ir Evaluationmentioning
confidence: 99%
“…Many forms of criteria and associated evaluation measures have emerged in the literature of user-oriented IR. For example, Wilson et al (2010) identify various criteria (and measures) that broadly reflect the levels identified in Section 2, but grouped into three contextual levels: (1) evaluation within the IR context; (2) evaluation within the information seeking context; and (3) evaluation within the work context. Kelly (2009) also identifies four basic measures: (1) contextual, that captures characteristics of the subject and tasks undertaken (e.g., age, gender, familiarity with search topics); (2) interaction, that captures aspects of the usersystem interaction (e.g., number of queries issued, number of documents viewed, etc.…”
Section: Criteria and Measuresmentioning
confidence: 99%
“…Also it is shown how the method outperforms both keyword-based search and pure semantic search in terms of precision and recall in a set of experiments performed on a collection of about 18,000 technical documents. Wilson et al [33] aims to exploratory search by focusing on the techniques and visualizations that allow users to interact with and have control over their findings. They have shown that there is substantial room for improving the support provided to users who are exhibiting more exploratory forms of search, including when users may need to learn, discover, and understand novel or complex topics.…”
Section: Related Workmentioning
confidence: 99%
“…It argues that flexible design, one that, for example, includes the S&F options, helps consumers find exactly what they need and want, that is, it makes their search considerably more efficient and effective (Baeza-Yates and Ribeiro-Neto, 1999;Yee et al, 2003;Kules et al, 2009). As this connection between human/computer interface design, consumer choice, and firm performance has been validated, it follows that investigating consumer behavior of web search interaction is key to improving the user interface (White and Drucker, 2007;Hearst, 2008;Wilson et al, 2010;Wilson, 2011;Ceri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%